WAS SUSRUTAS NASA-SANDHANA DEVELOPED INTO RHINOPLASTY? (International Journal of Ayurveda and Pharma Research, 2015)
Sushruta, a great ancient surgeon and philosopher, and above all a great teacher is considered as the father of surgery and the father of plastic surgery even today. He has compiled a monumental treatise on ancient surgery named Susruta samhita. Sushruta Samhita comprises description of training and practice of surgeons, surgical procedures, drugs of animal, plant and mineral origin. It also includes different surgical procedures including rhinoplasty and various kinds of instruments. Though many consider plastic surgery as a relatively new specialty, the origin of plastic surgery had its roots more than 4000 years old in India, back to the Indus River Civilization. The Gentlemans magazine of London provides us an evidence of an article published in 1794 regarding the procedure of Nasa-sandhana of Indian origin and its gradual development into rhinoplasty.